Marketing Communication Strategy of Pesona Maidah Bakery Based on Personal Selling in 2024 - Juliana, Silvia Ayu; Sudiwijaya, Erwan (Jogjakarta Communication Conference (JCC), 2025)
This study aims to describe the marketing communication strategy based on personal selling implemented by Pesona Maidah Bakery in 2024. Employing a descriptive qualitative approach, data were collected through structured interviews and field observations and analyzed using Miles and Huberman's model. The findings reveal that personal selling was carried out intensively and relationally by sales personnel through strong interpersonal approaches, including empathetic communication, suggestive persuasion techniques, product sampling, and attractive promotional offers. Sales agents actively targeted strategic locations such as traditional markets and public areas to find prospective customers, fostered emotional connections through informal conversations, and maintained customer loyalty via follow-up communication on WhatsApp. The product advantages communicated include the use of premium ingredients, absence of preservatives, and daily fresh production. The analysis indicates that this strategy effectively fosters emotional closeness, builds trust, and enhances customer loyalty. The personal selling strategy of Pesona Maidah Bakery reflects the principles of Relationship Marketing, emphasizing not merely transactional outcomes, but the development of long-term relationships with consumers through human-centered, adaptive, and consistent communication.